Growth temperature induced changes of luminescence in epitaxial BN: from colour centres to donor-acceptor recombination - Korona, K P; Binder, J; Dąbrowska, A K; Iwański, J; Reszka, A; Korona, T; Tokarczyk, M; Stępniewski, R; Wysmołek, A (Nanoscale, 2023)
Defects play a very important role in semiconductors and only the control over the defect properties allows the implementation of materials in dedicated applications. We present an investigation of the UV luminescence of defects in hexagonal boron nitride (h-BN) grown by Metal Organic Vapor Phase Epitaxy (MOVPE). Such intentionally introduced defects are important for applications like deep UV emission and quantum information. In this work, we performed photoluminescence and cathodoluminescence experiments on a set of h-BN layers grown by MOVPE at different growth temperatures ( ). The obtained defect-related spectra in the ultraviolet range include well-known lines at about 230 nm (X230, = 5.4 eV) and 300 nm (C300 - the brightest one, = 4.14 eV) as well as a rarely observed band with a zero-phonon line at 380 nm (C380, = 3.24 eV). The C300 and C380 bands have the characteristic of a color centre showing sharp lines (0.6 nm width) at 5 K. These lines are most probably an internal transition of carbon-related defects. We show that for samples grown at high temperatures ( > 1200 °C), the lines related to the color centres C are replaced by broad bands at 330 nm and 400 nm, which we marked as D330 and D400, respectively. The D bands have similar central energies to the C bands but extend over a large energy range, so we propose that the D emission is due to a shallow donor to deep acceptor recombination. Time-resolved photoluminescence analysis determined the lifetimes of the individual lines in the range from 0.9 ns (C300), 1.8 ns (C380) to 4 ns (D400). The C300 and C380 color centre bands are composed of a series of characteristic lines that are due to the interaction with phonons. The E (198 meV) and A (93 meV) phonon replicas have been identified.